2020
DOI: 10.1101/2020.05.26.116152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plis de passage in the Superior Temporal Sulcus: Morphology and local connectivity

Abstract: While there is a profusion of functional investigations involving the superior temporal sulcus (STS), our knowledge of the anatomy of this sulcus is still limited by a large variability across individuals. Several “plis de passage” (PPs), annectant gyri buried inside the fold, can separate the STS into distinct segments and could explain part of the observed variability. However, an accurate characterization is lacking to properly extract and fully understand the nature of PPs. The aim of the present study is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 72 publications
4
12
0
Order By: Relevance
“…In contrast, the middle and anterior macaque STS bumps extend into the fundus but are not contiguous with convolutions along the upper bank of the STS in most hemispheres. This discontinuity may be similar to "deep" plis de passages reported recently in the human STS that are partially disconnected in the fundus (36). A continuous bump extending to the upper bank was apparent only for the middle Monkeys, gibbons, and baboons.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the middle and anterior macaque STS bumps extend into the fundus but are not contiguous with convolutions along the upper bank of the STS in most hemispheres. This discontinuity may be similar to "deep" plis de passages reported recently in the human STS that are partially disconnected in the fundus (36). A continuous bump extending to the upper bank was apparent only for the middle Monkeys, gibbons, and baboons.…”
Section: Discussionsupporting
confidence: 84%
“…Although less studied in Old Word monkeys, such features are associated with functional specializations in humans (31,(33)(34)(35). Of particular note, several plis de passage (annectant gyri) in the human STS are thought to reflect distinct structural connectivity bridging superior and middle temporal gyri and functional specializations (35)(36)(37). Similar to these plis de passages, the macaque STS bumps 1) are convolutions buried in the main furrow of the STS, 2) are distributed along the posterior-to-anterior axis, 3) are consistent in their location across individuals, and 4) emerge early in development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while the tension-based theory of D. Van Essen to explain the folding pattern has been set aside regarding primary sulci (Van Essen 1997; Llinares-Benadero and Borrell 2019), fiber-based constraints may be one of the drivers of secondary and tertiary folding. Hence, the potential relationships between plis de passage and U-fiber bundle organization is a very attractive research program (Mangin et al 1998; Pron et al 2018; Bodin et al 2019). U-fiber organization must be impacted by the depth of plis de passage.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of "Pli de passage" (PPs) was introduced by Gratiolet (1854) to describe transverse gyri that interconnect both sides of a sulcus, are frequently buried in the depth of these sulci, and are sometimes apparent on the cortical surface. Several authors have pointed out that they provided an understanding of the variable interruptions in sulci across individuals, and it was recently demonstrated that PPs can be a useful morphological landmark for models of cortical foldings [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%